Biosecurity and readiness of smallholder pig farmers against potential African Swine Fever outbreak and other pig diseases in Baybay City, Leyte, Philippines - C. Bernardes, Divine Thea (2020)
Preventing African Swine Fever (ASF) outbreaks require an active involvement of pig growers as they are in the frontline of detection, notification, and the application of strict biosecurity measures. The Eastern Visayas (Region VIII) in Central Philippines is still free of ASF but the risk can be remarkable given the high volume of pigs that enter in this region as a market hub to large pig producers both coming from Luzon (north) and Mindanao (south). This study was conducted to better understand the readiness and biosecurity practices of smallholder pig farmers who comprise most of the pig growers in the City of Baybay, Leyte. Using multiple correspondence analysis (MCA) and agglomerative hierarchical clustering (AHC) technique of data from 350 pig farmer-respondents, our study found several areas in pig raising activities that need to be highlighted. While pig farmers were generally aware of the threat posed by ASF and have relatively good biosecurity practices, only 32.90% were convinced that the City of Baybay is prepared in the case of an ASF outbreak. Moreover, the importance of vaccination, footbath, and controlling swill feeding need to be emphasized (Cluster 2, 58.29%).  More efforts should be directed towards preparing and training pig farmers on disease monitoring and surveillance and improving further its biosecurity practices with special focus on bioexclusion. Similar studies should be conducted to nearby local government units particularly those located near entry and exit borders of the Eastern Visayas region.